Synthesis and characterization of Al foams produced by powder metallurgy route using dolomite and titanium hydride as a foaming agents - Paulin, Irena (Materiali in tehnologije, 2014)
Production of aluminum foams by the powder-metallurgy process depends on the preparation of pre-cursors. In general, pre-cursors consist of compacted mixture of metallic powder and foaming agent, which is foamed at a pre-determined temperature. Due to high temperature of foaming procedure, the foaming agent decomposes into a solid component that is built into the matrix material, and a gas component that causes foaming of the matrix material. Powder metallurgy is a method for making close-cell foams and it is the best selection, especially for the production of net-shape parts, providing excellent quality of end products. In our research work, powders, precursors and foams, made from different metallic powders (Al 99.7 % purity, AlSi12 alloy) with different foaming agents (TiH2, CaCO3, CaMg(CaCO3)2), were examined with different analytical techniques.
Keywords: Al alloys; Al-zlitine; powder metallurgy; prašna metalurgija; penilna sredstva; foaming agents; pene; close-cell foams; zaprta poroznost